Trends in Drought Research - Rainer Messmer; Peter Stamp (Agriculture and Natural Resources, 2010)
Drought is already a major abiotic constraint to global food production. Climate change will further aggravate this situation. Moreover, the expected increase in the world’s population over the next decades will pose huge challenges to food production as the available water per capita decreases. Although several methods have been developed, it remains difficult to judge where water is and whether it will be scare. Technological improvements will allow for more efficient irrigation. At the same time, it is vital to develop genetically improved crops, which produce higher yields under drought conditions. This can be achieved by increasing their yield potential and by reducing the gap between the maximum yield potential and yield under drought. For example, considerable progress has been made in the genetic improvement of temperate and tropical maize. Future progress will depend on newly defined secondary traits involved in the aerial morphology of plants, in the development and the architecture of the root system, and in physiological mechanisms that confer drought tolerance. There are many techniques available to achieve a better understanding of the complex network of plant responses to drought and to manipulate these responses. These techniques include the mapping of quantitative trait loci (QTLs), association mapping, studies of gene expression and genetic transformation. Although it is unlikely that single genes, especially genes protecting primary metabolism, will greatly enhance plant productivity in the field, some results are encouraging. The success of these technologies will depend on a multidisciplinary approach combining physiology, quantitative genetics, genomics and breeding. Moreover, the agronomical, socio-economical and political context must be considered in order to meet the tremendous challenges to crop improvement.